Endoscopic Procedures In Patients Taking Novel Oral Anticoagulants - Raluca Anica IONESCU; Andreea GHIDERSA; Roxana SADAGURSCHI; Lucian NEGREANU; Ruxandra BABIUC (Modern Medicine)
The use of direct oral anticoagulants (DOAC) for the treatment of atrial fibrillation and prevention of strokes is encouraged by their superior properties compared to vitamin K antagonists: predictable anticoagulant effect, greater patient compliance, few drug interactions, low risk of intracranial hemorrhages. Although practicing gastroenterologists may never prescribe a DOAC, they are likely to encounter DOAC-related GI adverse events (gastrointestinal bleeding), and they will need to manage DOACs around the time of endoscopy. The present paper aims to present the management possibilities of the patient treated with DOAC undergoing endoscopy, most studies performed so far focusing on the risk of spontaneous bleeding in this category of subjects. The current guidelines provided by the British Society of Gastroenterology and the European Society of Gastrointestinal Endoscopy orientate us, but endoscopic maneuvers should be preceded by a detailed analysis of the risks of secondary bleeding and thrombosis associated with DOAC users.